2014
DOI: 10.3389/fsurg.2014.00048
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Infant Mortality Rate among Dutch Oral Cleft Cases: A Retrospective Analysis from 1997 to 2011

Abstract: Objectives: First, to determine the infant mortality rate (IMR) for Dutch patients with isolated oral clefts (OC) as well as for patients with clefts seen in association with other malformations. Second, to conduct a similar analysis per cleft type: cleft lip with or without cleft palate (CP), CP (including Robin sequence). Third, to examine the underlying causes of death.Material and Methods: A retrospective review of the charts of patients with OC born in the period 1997–2011 and treated in three regional cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…Our reported mortality rate is in line with the previously described mortality rates in RS infants, which range from 2 to 26% [ 9 , 11 , 12 , 14 , 15 , 19 , 21 , 29 , 32 , 33 , 35 , 37 ], although it was higher than what we expected when the study was initiated. Our group of deceased infants consists of a highly heterogeneous group (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our reported mortality rate is in line with the previously described mortality rates in RS infants, which range from 2 to 26% [ 9 , 11 , 12 , 14 , 15 , 19 , 21 , 29 , 32 , 33 , 35 , 37 ], although it was higher than what we expected when the study was initiated. Our group of deceased infants consists of a highly heterogeneous group (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Clinicians mainly focus on the morbidities of RS, which include respiratory complications due to upper airway obstruction, feeding problems, a related failure to thrive, and the associated cleft palate problems, when present [ 10 , 16 , 33 ]. Reported mortality rates in RS vary from 2 to 26% [ 9 , 11 , 12 , 14 , 15 , 19 , 21 , 29 , 32 , 33 , 35 , 37 ]. Upper airway management plays a central role in the treatment of RS.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al found a 15 times greater risk of mortality in CPO patients when compared to the general population, and a 10 times greater risk when compared to other types of clefts (Kang et al, 2012 ). A 14-year study of Dutch patients found an infant mortality rate (IMR) of 2.45% for all CPO, with the most common cause of death for all oral clefts being congenital malformations of the heart (40.6%; van Nunen et al, 2014 ). Congenital heart defects commonly present with oral clefts, and are reported to occur in 1.3 to 27% of affected individuals, although the mechanism is still unknown (Setó-Salvia and Stanier, 2014 ).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…A national study of Dutch infants with orofacial clefts reported the overall IMR to be elevated at 2.09%, which was signi cantly higher than the Dutch general population IMR of 0.45% [28]. In another report by the East of England Cleft Network of 638 children with clefts, the causes of deaths were reported to be from associated anomalies (61%) and infections (17%), and the IMR was 3.6% for children with clefts [29]. The IMR for children with clefts in all studies was consistently higher than that of the general population.…”
Section: Neonatal and Infant Mortality Ratementioning
confidence: 95%